UPAYA KEBIJAKAN DAN PERMASALAHAN AKSES PENDIDIKAN DASAR - Rizki Ananda; Husnul Latifah; Aura Afrillia Anry; Jihan Ashilah; Ahmad Rifaldi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article discusses the policies and issues related to access to basic education in Indonesia, which is a crucial aspect of national development. Education serves to develop human potential and improve the quality of human resources. Although the government has implemented various policies, challenges such as curriculum relevance, unequal distribution of teachers, and limited ongoing training continue to hinder the achievement of national education goals. Through a literature review approach, this article identifies the root causes and contributing factors to the low quality of education, including structural issues, human resources, and socio-cultural factors. Strategic recommendations are proposed to improve education quality, such as enhancing curriculum relevance, equalizing teacher distribution, and reducing administrative burdens. With the implementation of appropriate policies, it is expected that access to and the quality of basic education in Indonesia can improve significantly.